Exploring the Introduction of Computational Thinking in STEM Education in Australian Schools - Dorian Stoilescu (Southeast Asian Mathematics Education Journal, 2019)
This paper discusses theoretical and curricular aspects of computational thinking in curriculum and detects recent perspectives and challenges noticed in introducing computational thinking in STEM in Australian Schools. It presents the way computational thinking is defined and understood in curriculum documents and a set of relatively new implementations that were designed nationally and in the state of New South Wales. This paper uses qualitative research methods such as content analysis and text analysis. The research analyses some recent trends in introducing computational thinking and explores these reforms that are described in the official documents. It was noticed that although the importance of computational thinking was highly emphasized, the documents cannot describe a consistent implementation of this set of educational policies, as at this time implementing computational thinking is largely underperforming. It is recommended a more systemic way of designing policies and curriculum content for the integration of computational thinking in Australian schools is needed. Future research needs to explore reasons for delaying these reforms of introducing computational thinking.